EMQs in ophthalmology, dermatology and ENT an essential revision guide with comprehensive answers - Bizrah, Mukhtar; Khatib, Manaf (MasterPass, 2013)
This unique text presents challenging questions covering common and important ophthalmology, dermatology and ENT topics. The comprehensive answers make it an all-in-one study and revision tool for busy students.These specialties are commonly misunderstood by medical students and clinical trainees, and are known to be areas in which valuable marks are frequently lost in written and clinical examinations